2022
DOI: 10.3390/d14110948
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Based Taxa Delimitation (GBTD): A New Approach

Abstract: Proper taxonomic identification is essential for biological research. Unfortunately, there are no clear guidelines for taxonomic assignment above the species level. Here, we present a novel approach—GBTD—to the use of genetic divergence to evaluate the taxonomic position of certain samples with simultaneous estimation of the current systematics correctness. This approach includes measuring the raw and model-adjusted distances between DNA sequences and attributing them to the lowest taxonomic levels that are co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…Our new results together with a review of the body of literature [5,7,8,28,32] indicate that the genus Glossiphonia represents a rather species-rich clade of freshwater leeches, which currently contains no less than 16 valid species (Table 2). The taxonomic status of these species was already confirmed by means of a DNA-based approach, except for Glossiphonia paludosa, G. pulchella, and G. slovaca, whose sequences are unavailable.…”
Section: Taxonomic Noveltiesmentioning
confidence: 67%
See 4 more Smart Citations
“…Our new results together with a review of the body of literature [5,7,8,28,32] indicate that the genus Glossiphonia represents a rather species-rich clade of freshwater leeches, which currently contains no less than 16 valid species (Table 2). The taxonomic status of these species was already confirmed by means of a DNA-based approach, except for Glossiphonia paludosa, G. pulchella, and G. slovaca, whose sequences are unavailable.…”
Section: Taxonomic Noveltiesmentioning
confidence: 67%
“…Comments: It was found that the type species of both glossiphoniid genera, which were thought to be endemic to Lake Baikal (Baicaloclepsis and Paratorix), belong to the Glossiphonia clade [27,28]. Hence, these genus-group names are junior synonyms of Glossiphonia, and the species they contain must be transferred to the latter genus as follows: G. baicalensis (Stschegolev, 1922) Comments: It was found that the type species of both glossiphoniid genera, which were thought to be endemic to Lake Baikal (Baicaloclepsis and Paratorix), belong to the Glossiphonia clade [27,28]. Hence, these genus-group names are junior synonyms of Glossiphonia, and the species they contain must be transferred to the latter genus as follows: G. baicalensis (Stschegolev, 1922), G. echinulata (Grube, 1871) comb.…”
Section: Taxonomic Accountmentioning
confidence: 99%
See 3 more Smart Citations